-5n-5(-7-2n)=

Simple and best practice solution for -5n-5(-7-2n)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5n-5(-7-2n)= equation:


Simplifying
-5n + -5(-7 + -2n) = 0
-5n + (-7 * -5 + -2n * -5) = 0
-5n + (35 + 10n) = 0

Reorder the terms:
35 + -5n + 10n = 0

Combine like terms: -5n + 10n = 5n
35 + 5n = 0

Solving
35 + 5n = 0

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-35' to each side of the equation.
35 + -35 + 5n = 0 + -35

Combine like terms: 35 + -35 = 0
0 + 5n = 0 + -35
5n = 0 + -35

Combine like terms: 0 + -35 = -35
5n = -35

Divide each side by '5'.
n = -7

Simplifying
n = -7

See similar equations:

| E=0.14x^2+7.8x+540 | | -10(t-6)+116-16=108 | | 5x^9/8-15=0 | | 3600+x^2+144=x^2 | | 4(3x-2)/7=4 | | 178w=-1114 | | 2x-6=116 | | x-(-14)=34 | | 3x-2+2=6+2 | | 5-(b+3)=-1+2(b-3) | | 13-(8x)+4x-(-12)= | | x^2+25x-300=0 | | 5x+2(5x-15)=60 | | -6v=-16v+30 | | 10-16x=-230 | | 4-6(4n+1)= | | x/4=x/5-7 | | 6(-2+7x)+4x=36-2x | | 2(2.5x-5)+2= | | -8a+10=-8(a+3) | | n=-3/8=1/8 | | 2+(5+y)=0 | | 9(-8-2p)= | | -4+8(p+4)=4(4p-1) | | 15-9/3=-9 | | 14x-14=16x | | 10-3a=40 | | 81[(5+3)-5]= | | Y^2-9y=-18 | | 4t+9= | | -4(5-4x)=-40+6x | | -7=a-7 |

Equations solver categories